Clients' Attributions of the Presenting Problem and the Therapeutic Alliance in Couple Therapy: Systemic Versus Intrapersonal Perspectives. (27th April 2020) - Wu, Qiong; McWey, Lenore M.; Ledermann, Thomas
Abstract : The therapeutic alliance is central to couples' therapy success. The current study examined associations between couples' initial agreement and causal attributions of the presenting problem and changes in the therapeutic alliance. To test study hypotheses, 85 couples were recruited from a university training clinic focused on couple and family therapy. Couples completed an intake questionnaire concerning their attribution of the presenting problem, either as systemic or individual, and therapeutic alliance was assessed at the end of sessions 2–8. A dyadic multilevel model revealed that a disagreement in the couple's attributions of the problem (with one viewing it as systemic, the other as individual) was associated with a larger initial discrepancy in the couple's therapeutic alliance, as well as a decline in the discrepancy over time. Findings were discussed in the context of systemic family theory, with implications for improving assessment, treatment, and psychoeducation aimed toward couples in distress.